INTERAKSI SOSIAL ASOSIATIF EKS PENDERITA KUSTA DI DUSUN SUMBERGLAGAH, KABUPATEN MOJOKERTO - Rena Ratri Anggoro; Mochammad Bagus Qomaruddin (Universitas Airlangga, 2019)
Ex-leprosy patients still got stigma and discrimination from community although they had been cured. The stigma from community has been raising psychological and social problems that can affect their social interaction. This study aimed to describe associative social interactions of ex-leprosy patients in Sumberglagah Village of Mojokerto Regency based on the concept of social health aspect. The study employed descriptive qualitative method with the data collection techniques including observation, interview, and documentation. The instrument used in this study was interview guidelines. In this case, interview was conducted with 11 informants consisting of 8 ex leprosy patients as informants and 3 public figures as key informants. Informants were chosen based on characteristics that had been determined by the researcher. Besides, aspects examined in this study included cooperation, accommodation, and assimilation between ex-leprosy patients and other communities. Data were analyzed through several phases including reduction, data presentation, and drawing the conclusion. The results showed that first, the form of coorporation occurring between ex-leprosy patients and other communities was a bargaining process. Second, accomodation that occurred between ex-leprosy patients and other communities was tolerance. In this circumstance, ex-leprosy patients served the other communities with wrapped drinks and foods. Third, the assimilation aspect was marriage. It could be concluded from the study that the associative interactions that occurred couldrealize the patterns of good social interaction to support the realization of goodsocial health conditions for ex-leprosy patients in Sumberglagah Village.